Latent tuberculosis treatment completion rates from prescription drug administrative data - Plourde, Pierre J. (Can J Public Health, 2019)
OBJECTIVE: In the province of Manitoba, Canada, given that latent tuberculosis infection (LTBI) treatment is provided at no cost to the patient, treatment completion rates should be optimal. The objective of this study was to estimate LTBI treatment completion using prescription drug administrative data and identify patient characteristics associated with completion. METHODS: Prescription drug data (1999–2014) were used to identify individuals dispensed isoniazid (INH) or rifampin (RIF) monotherapy. Treatment completion was defined as being dispensed INH for ≥ 180 days (INH180) or ≥ 270 days (INH270) or RIF for ≥ 120 days (RIF120). Logistic regression models tested socio-demographic and comorbidity characteristics associated with treatment completion. RESULTS: The study cohort comprised 4985 (90.4%) persons dispensed INH and 529 (9.6%) RIF. Overall treatment completion was 60.2% and improved from 43.1% in 1999–2003 to 67.3% in 2009–2014. INH180 showed the highest completion (63.8%) versus INH270 (40.4%) and RIF120 (27.0%). INH180 completion was higher among those aged 0–18 years (68.5%) compared with those aged 19+ (61.0%). Sex, geography, First Nations status, income quintile, and comorbidities were not associated with completion. CONCLUSIONS: Benchmark 80% treatment completion rates were not achieved in Manitoba. Factors associated with non-completion were older age, INH270, and RIF120. Access to shorter LTBI treatments, such as rifapentine/INH, may improve treatment completion.